THE IMPACT OF PROACTIVE PERSONALITY ON CREATIVE BEHAVIOUR EXAMINING THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND THRIVE AT WORK (Contemporary Journal of Social Science Review, 2025)
Employee creativity is a cornerstone of organizational innovation and competitive advantage. This study investigates the interplay between proactive personality, transformational leadership, and thriving at work in fostering creative behavior. Drawing on a mixed-methods approach, we analyze survey data from a diverse sample of employees across industries to explore how thriving at work mediates the relationship between proactive personality and creativity, and how transformational leadership moderates this dynamic. Our findings reveal that proactive individuals thrive in supportive environments, which in turn enhances their creative output. Transformational leadership amplifies this effect by fostering psychological safety and intrinsic motivation. The study contributes to the literature by integrating social cognitive and conservation of resources theories, offering practical insights for leadership development and organizational interventions aimed at cultivating innovation.